Successful Use of Infliximab Therapy in Sight-threatening Corticosteroid-resistant Vogt-Koyanagi-Harada Disease. (August 2013) - Zmuda, Mathieu; Tiev, Kiet Phong; Knoeri, Juliette; Héron, Emmanuel
<x xml:space="preserve">Abstract</x> Purpose: To report an experience with infliximab in severe corticosteroid-resistant Vogt-Koyanagi-Harada (VKH) disease. Design: Interventional case series. Methods: The medical records of 2 adult patients were reviewed. Results: Both patients had a visual acuity reduced to hand motion perception bilaterally after 1 month of high-dose corticosteroid therapy, due to multiple exudative retinal detachment involving the fovea. Visual acuity and OCT findings improved immediately after the first infliximab infusion, retinal detachments fully resolved after 1 month and visual acuity returned to normal within 6 months. Despite a negative pretreatment screening, one patient developed multivisceral tuberculosis, which led to infliximab discontinuation after the 7th infusion and was cured by a 9-month ambulatory antibiotic regimen. The other patient received 11 well-tolerated infliximab infusions. Respectively, 9 and 4 months after infliximab discontinuation both patients had normal vision and OCT findings. Conclusion: Infliximab showed tremendous therapeutic efficacy in sight-threatening corticosteroid-resistant VKH disease.